Dosage consideration for transcranial direct current stimulation in post-stroke dysphagia: A systematic review and network meta-analysis - Xie, Jianwei; Zhou, Chiteng; Ngaruwenayo, Gilbert; Wu, Minghui; Jiang, Xiaoyu; Li, Xiaohan (Frontiers in Neurology, 2023)
Objective This systematic review and network meta-analysis sought to determine the efficacy of different intensities of transcranial direct current stimulation (tDCS) in patients with dysphagia after stroke to improve swallowing function. Methods Randomized-controlled trials (RCTs) of tDCS in post-stroke dysphagia were searched from Pubmed, EMBASE, Cochrane Library, Web of Science, China National Knowledge Infrastructure (CNKI), Chinese Biomedical Literature Service System (SinoMed), Wanfang database, and Chinese Scientific Journals Database (VIP) from databases' inception to June 22, 2022. Article screening, data extraction, and article quality evaluation were completed by 2 independent researchers. Network meta-analysis was performed using Stata. Results A final total of 20 studies involving 838 stroke patients were included. The included control interventions were sham tDCS and conventional therapy (CT). Network meta-analysis showed that 20 min of 1.2, 1.4, 1.5, 1.6, and 2 mA anodal tDCS and 30 min of 2 mA anodal tDCS significantly improved post-stroke dysphagia compared with CT (all P < 0.05). In addition, 20 min of 1, 1.4, 1.6, and 2 mA anodal tDCS also significantly improved post-stroke dysphagia compared with sham tDCS (all P < 0.05). Our results demonstrated that 20 min of stimulation at 1.4 mA was the optimal parameters for anodal tDCS and exhibited superior efficacy to CT [SMD = 1.08, 95% CI (0.46, 1.69)] and sham tDCS [SMD = 1.45, 95% CI (0.54, 2.36)]. Conclusion Different durations and intensities of anodal tDCS are effective in improving post-stroke dysphagia. However, 20 min of tDCS at 1.4 mA may be the optimal regimen. Systematic review registration https://www.crd.york.ac.uk/PROSPERO/#recordDetails, identifier CRD42022342506.